Effectiveness Directorate General Taxes Online Invoice Management System on Financial Taxes at the Directorate of Research and Community Service, Bandung Institute Technology - Yanti, Sindi; Rosmayati, Siti (Coopetition : Jurnal Ilmiah Manajemen, 2025)
This study aims to evaluate the effectiveness of the invoice management system at DRPM ITB in supporting tax compliance and efficiency. The system integrated with Directorate General of TaxationOnline is expected to reduce tax calculation errors and improve financial administration. With a qualitative case study approach, this study involved interviews, observations, and documentation analysis. The results showed benefits in efficiency, transparency, and accessibility. The SWOT analysis identified strengths, weaknesses, opportunities, and threats. Suggestions for improving effectiveness included ongoing training, infrastructure improvements, and policy monitoring. Overall, the Directorate General of TaxationOnline system has contributed to more transparent and accountable tax management, although continuous improvement is needed. Top of FormBottom of Form Keywords: Invoice management system, Directorate General of TaxationOnline, financial administration, DRPM ITB.